If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(3x)=9x-4
We move all terms to the left:
-(3x)-(9x-4)=0
We get rid of parentheses
-3x-9x+4=0
We add all the numbers together, and all the variables
-12x+4=0
We move all terms containing x to the left, all other terms to the right
-12x=-4
x=-4/-12
x=1/3
| 2(u-5)-6=-3(-5u+8)-u | | 1=6-2c | | -12b+-2b+7b+-2=12 | | 4(c-15)=-12 | | -12b+-2b—7b+-2b=12 | | 102-v=252 | | 6g-4=4g+1 | | 3.5d+9.75=1+5.25 | | -3-5n+4n=15 | | 300+2x=360 | | 19=-4t-5 | | z/5+8=-55 | | z/9+5=-18 | | 19x-9=4x+30 | | 17-2n=1-4n+4 | | 6+6v=9v | | 19x-9=4x-30 | | 1.1x=0.5*0.8-x | | x^2−2x=2x+32 | | 15-5x=-6x | | 15/h−17=−13 | | z/9+5=18 | | 5w=10w−5 | | h/15−17=(−13) | | h/15−17=−13 | | (3x+8)/2-6=4 | | 4a+12=2a+6 | | k/4+2=22 | | 1.1x=0.5*(0.8-x) | | -2k−8=10+4k | | b+10=13+b+5-8 | | 2z+37=4z |